Propriedades espectroscópicas e mecanismos da oxidação da levodopa e carbidopa - Cardoso, Thaís Duque (2021)
Parkins on's disease (PD) is characterized by a decreas ing of dopamine in the brain. This disease affectsmainly people over 60 years and its treatment is carried out using levodopa (L dopa), which acts as a neurotransmitter , being converted into dopamine in the b rain. In the first treatments using this drug, there were several side effects, such as nausea, vomiting and orthostatic hypotension, which were frequent due to the conversion of L dopa into dopamine in the peripheral regions of the brain. To overcome these effects, L dopa began to be administered together with carbidopa (C dopa), which is an inhibitor of thedopa decarboxylaseenzyme, which makes this conversion outside the central nervous system. The simultaneous dosage of these two active drugs in pha rmaceutical formulations is of great importance to optimize their therapeutic efficienc iesand to minimize their side effects. In this work, the experimental and theoretical analyses were performed using the ultraviolet visible (UV Vis) electron absorption spectroscopy to optimize a simple, low cost, and efficient experimental method for the simultaneous dosage of L dopa and C dopa. In addition, systematic analy s es based on time dependent and time independent density functional theories (TD DFT and DFT) were conducted to determine the oxidation mechanisms of each drug. Theoptimizedmethod consists of dissolution of L dopa and C dopa in HCl , with subsequent addition of NaOH, which led s to oxidation of the analyzed species. The UV Vis spectra in both cases allow ed the simultaneous dosage of active principles, providing the basis for the theoretical investigation of the reaction mechanisms involved in the oxidation process es of these species. Different reaction mechanisms were evaluated for L dopa and C dopa, and the DFT and TD DFT results indicate d that the employed methodology was able to efficiently reproduce the experimental UV Vis spectra of non oxidized (in HCl) and oxidized with NaOH), L dopa and non C dopa showing small differences in intensities and displ acements of the maximum absorption peaks of bands , which can be ascribed by solvent effects, which were not taken into account in the spectrum calculations. With regard to L dopa, the TD DFT results show ed favorable thermodynamic al conditions for oxidation mechanism of L dopa, which has been previously proposed in the literature by Mandrakian et. al . However, t he final species identified in solution was the zwitterionic intermediate, which has an absorption band in the visible region. Among three investigated mechanisms for C dopa, the most favorable thermodynamical mechanism was th at with the final oxidized species correspond ingthe zwitterionic intermediate, where a new five membered aromatic ring was formed . In general, the present study has indicate d that the theoretical and experimental analyses as one useful tool in the investigation of reaction mechanisms involving molecular systems with pharmacological interest